Real-time optoacoustic tomography of indocyanine green perfusion and oxygenation parameters in human finger vasculature - Lutzweiler, Christian; Meier, Reinhard; Rummeny, Ernst; Ntziachristos, Vasilis; Razansky, Daniel (Optics Letters, 2014)
We interrogated whether optoacoustic tomography could be employed to study blood functional parameters and biodistribution of injected fluorescent agents in humans. Using a multichannel scanner at a frame rate of 10 images per second, we obtained cross-sectional images of the human finger in real time, before and after the administration of indocyanine green. We demonstrated that multispectral optoacoustic tomography can sense fast flow kinetics and resolve spatiotemporal characteristics of a common fluorochrome in human vasculature at clinically relevant concentrations. We further register ICG images with oxygen saturation maps and anatomical views of the proximal interphalangeal joint of a healthy volunteer. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2023-03-08